Conference on research in business finance - Universities--National Bureau Committee for Economic Research (New York : National Bureau of Economic Research, 1952)
This book consist of several papers presented at a conference. The first dealt with the broad statistical framework of sources and uses of funds of American business; the several papers combined represented an attempt to indicate what we know, and what we still have to learn regarding the flow of funds through business firms. The second group of papers included a collaborative effort covering the general problem of projecting business capital requirements. The final set of papers presents theoretical analyses, supported by certain empirical tests, of the relationship between business demand for capital funds and the costs of obtaining this funds.
Includes bibliographical footnotes and index.
hza 07/08/2018
Loans
Keywords: Finance; Corporations